1979
DOI: 10.1007/bf00289443
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomes in acute leukemia

Abstract: The karyotype of leukemic cells of 78 acute leukemia patients (37 ANLL, 34ALL, and 7 of unknown type) was studied by means of G-banding. Chromosomal abnormalities were found in 50 patients (72%). Chromosomes 8,21,5,7,11, and 19 were preferentially involved in the abnormalities, both in ANLL and in ALL. A high incidence of the characteristic rearrangement t(8;21) was noted in AML: (in 6 of 22 AMP patients). An identical reciprocal translocation--t(4;11)--was seen in 4 out of 34 ALL patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

1981
1981
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(21 citation statements)
references
References 18 publications
1
18
0
2
Order By: Relevance
“…10,11,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] The fact that six of the leukemias (3%) were morphologically classified as AML is also in line with what has been reported before. In fact, out of the 362 published cases with t(4;11), 11 (3%) have been AML, the majority AML-M4 and AML-M5.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…10,11,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] The fact that six of the leukemias (3%) were morphologically classified as AML is also in line with what has been reported before. In fact, out of the 362 published cases with t(4;11), 11 (3%) have been AML, the majority AML-M4 and AML-M5.…”
Section: Discussionsupporting
confidence: 75%
“…Clinical hallmarks of t(4;11)-positive leukemia include young age at presentation, hyperleukocytosis, hepatosplenomegaly, relatively high frequency of CNS involvement, overrepresentation of females, and poor response to therapy. 10,11,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] The blast cells have, by morphologic, cytochemical, ultrastructural, molecular genetic and immunologic means, been shown to display a mixture of lymphoid and myeloid features, suggesting that the cell of origin is an early progenitor with the potential for both lymphoid and myelomonocytic differentiation. Most leukemias are classified morphologically, using standard light microscopic criteria, as ALL of L1 or L2 type, although a few cases of acute myeloid leukemias (AML), mostly myelomonocytic, have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the t(11;19)(q23;q13) translocation is a very rare but recurrent aberration observed in acute myeloid leukemia (AML), acute lymphoblastic leukemia (ALL) and myelodysplastic syndromes (MDS): only 6 cases have ever been reported [2,3,4,5,6,7,8]. Recently, Yang et al [8] demonstrated that MLL was fused to ACTN4 , encoding an ubiquitously expressed actin-bundling protein at 19q13 by t(11;19)(q23;q13.1) in therapy-related MDS.…”
Section: Figmentioning
confidence: 99%
“…[2][3][4] Even before this, cytogeneticists had noted that translocations affecting the locus 11q23, and in particular the translocation t(4;11), characterize a special subset of ALL that was associated with poor survival. [5][6][7] Soon thereafter it became clear that these translocations of the locus 11q23 are also typical for mixed lineage leukemia. Whereas treatment of non-mixed lineage leukemia in children has become the textbook success story of modern medicine with 5-year survival rates approaching 90%, 8 mixed lineage leukemia treatment seems to have hit a roadblock with hardly 40% of all infants surviving five years after diagnosis ( Figure 1).…”
mentioning
confidence: 99%